Artesunate Nanoplatform Targets the Serine–MAPK Axis in Cancer‐Associated Fibroblasts to Reverse Photothermal Resistance in Triple‐Negative Breast Cancer - Zheng, Dongdong; Yan, Jiaqi; Liu, Xuejiao; Zhang, Zhiming; Jin, Anqi; Zhao, Yue; Bai, Lu; Quan, Mengyao; Qi, Xiuzhu; Fu, Bin; Wu, Zhigang; Zhou, Jin; et al. (Wiley, 2026)
Cancer-associated fibroblasts (CAFs) play a pivotal role in inducing photothermal therapy (PTT) resistance of triple-negative breast cancer (TNBC), but with unclear mechanism. Herein, aminoethyl anisamide-modified nano-biomimetic low-density lipoprotein (A-aLDL) is used to target deliver the PTT agent and artesunate (ARS) to both CAFs and cancer cells. Though CAFs are sensitive to PTT and notably transition to heat-resistant phenotype, the formed protective barrier is destroyed by ARS. Subsequently, the outstanding anti-tumor effects are achieved through PTT in multiple models with such kind of combination therapy. Interestingly, the mechanism is discovered that serine metabolism plays a major role in CAF resistance through spatially omics. ARS disrupts serine homeostasis, thereby attenuating the cascade activity of GTPases in MAPK pathway. Meanwhile, MAP2K7 is the most potential target for sensitizing PTT. By integrating ARS with PTT agents, the serine-MAPK axis in CAFs is successfully modulated, thereby overcoming PTT resistance in TNBC therapy.